2014
DOI: 10.1016/j.ajog.2013.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the need for and acceptability of a free-of-charge postpartum HPV vaccination program

Abstract: OBJECTIVE Human papillomavirus (HPV) vaccine uptake rate among young adult US women was only 23% in 2010. One way to improve this low rate is to administer the vaccine postpartum. We examined whether this population requires vaccination and whether they would be agreeable to receiving it free of charge after delivery. STUDY DESIGN Women 26 years of age or younger seeking prenatal care in publicly funded clinics in southeast Texas were interviewed in 2012 regarding their HPV vaccination status, barriers to va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…At our institution, only 13% among 500 pregnant patients seen in public clinics in 2012 had initiated the HPV vaccine. 12 These low rates may be due to a lack of routine care among low-income adolescents and young adult women. 13 Most US women do obtain medical care during pregnancy, 14 but the HPV vaccine is not usually discussed during prenatal care as it is not administered during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…At our institution, only 13% among 500 pregnant patients seen in public clinics in 2012 had initiated the HPV vaccine. 12 These low rates may be due to a lack of routine care among low-income adolescents and young adult women. 13 Most US women do obtain medical care during pregnancy, 14 but the HPV vaccine is not usually discussed during prenatal care as it is not administered during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, programs such as Vaccine for Children may have contributed to the relatively higher vaccination coverage that is seen in low-income groups. Other studies have found that Hispanic women have low levels of HPV knowledge and HPV vaccine awareness and low HPV vaccination rates compared to non-Hispanic women in the US [15, 1820]. Meanwhile, data from the US 2010 National Health Interview Survey show that non-Hispanic whites, English-speaking parents, individuals born in the US, and individuals from relatively higher income families were more likely to be aware of the HPV vaccine [21].…”
Section: Introductionmentioning
confidence: 99%
“…Provider recommendation for HPV vaccination is associated with increased vaccination 7,12 and prior research suggests that women find it acceptable to be offered and receive the HPV vaccine postpartum. 15,16 For any pregnant woman who has not received the vaccine before pregnancy, administration postpartum should be recommended and offered.…”
Section: Discussionmentioning
confidence: 99%
“…For women who have not previously received the HPV vaccine, the postpartum period may present an opportunity to vaccinate. Two studies have shown that women find it acceptable to be offered the HPV vaccine postpartum 15,16 and the majority of those who are interested (95%) initiate the vaccine. 16 The extent to which eligible women are initiating HPV vaccination postpartum is unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation